Bedside prediction of right subclavian venous catheter insertion length - Choi,Yoon Ji (2014)
Background and objective: The present study aimed to evaluate whether right subclavian vein (SCV) catheter insertion depth can be predicted reliably by the distances from the SCV insertion site to the ipsilateral clavicular notch directly (denoted as I-IC), via the top of the SCV arch, or via the clavicle (denoted as I-T-IC and I-C-IC, respectively). Method: In total, 70 SCV catheterizations were studied. The I-IC, I-T-IC, and I-C-IC distances in each case were measured after ultrasound-guided SCV catheter insertion. The actual length of the catheter between the insertion site and the ipsilateral clavicular notch, denoted as L, was calculated by using chest X-ray. Results: L differed from the I-T-IC, I-C-IC, and I-IC distances by 0.14±0.53, 2.19±1.17, and -0.45 ±0.68 cm, respectively. The mean I-T-IC distance was the most similar to the mean L (intraclass correlation coefficient = 0.89). The mean I-IC was significantly shorter than L, while the mean I-C-IC was significantly longer. Linear regression analysis provided the following formula: Predicted SCV catheter insertion length (cm) = -0.037 + 0.036 × Height (cm) + 0.903 × I-T-IC (cm) (adjusted r2 =0.64). Conclusion: The I-T-IC distance may be a reliable bedside predictor of the optimal insertion length for a right SCV cannulation.